Neural mechanism of the relationship between sleep efficiency and clinical improvement in major depressive disorder: A longitudinal functional magnetic resonance imaging study - Chen, Tao; Zhao, Wenming; Zhang, Yu; Yu, Jiakuai; Wang, Ting; Zhang, Jiajia; Li, Yifei; Zhu, Jiajia; Zhu, Dao-min (Frontiers in Psychiatry, 2022)
Background Antidepressants represent the most common treatment of choice for major depressive disorder (MDD). In this study, we aimed to explore the status-related changes (acute vs. remitted status) in brain function in patients with MDD. Methods Regular antidepressant medications (an average of 7 months after the initial visit, remitted status) were received by 48 patients with MDD. All the patients underwent MRI and polysomnography examinations as well as clinical assessment at each visit. Results We found that baseline fractional amplitude of low-frequency fluctuations (fALFF) of right superior parietal gyrus (SPG) and middle frontal gyrus could predict depression and anxiety symptoms improvement from acute to remitted status in patients with MDD, respectively. Moreover, we found a significant positive correlation between the fALFF of right SPG and baseline sleep efficiency (SE) in patients with MDD. Further mediation analysis revealed that the fALFF of right SPG mediated the relationship between baseline SE and depressive symptom improvement. Conclusion Apart from highlighting the fALFF as a potential prognostic indicator to predict and track disease progression in patients with MDD, these findings might provide a neural mechanism basis for improving sleep quality of patients with MDD and thus promoting the recovery of clinical symptoms, as well as provide a practical basis for clinical interventions in patients with MDD with sleep disorders.